PERLINDUNGAN HUKUM TERHADAP WANITA BERKEWARGANEGARAAN INDONESIA YANG MENIKAH DENGAN PRIA BERKEWARGANEGARAAN ASING TERHADAP KEPEMILIKAN PROPERTI DI INDONESIA - Yulia Resa Simorangkir; M. Yamin -; Rosnidar Sembiring -; Idha Aprilyana Sembiring - (jurnal.unprimdn.ac.id, 2021)
It is explained in the Constitutional Court’s Ruling No. 69/PUU-XIII/2015 that it is hearing a constitutional case of Mrs. Ike Farida. In this case, the petitioner has been legitimately married with a Japanese man. She bought an apartment on May 26, 2012 with the status of ownership. The problem was that after she had paid off and settled up the installment, the apartment was not handed in to her. Moreover, the contract was unilaterally revoked by the developer, arguing that her husband was a foreigner and she did not have any marriage agreement.